IMPLEMENTASI PERATURAN DAERAH NO 10 TAHUN 2012 TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN / KEBERSIHAN DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Mutmainah '; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated problems of implementation of the Regional Regulation No. 10 of 2012 on Service Fees Waste / Hygiene where the amount of garbage strewn on the roadside, waste transportation process is not routinely done, and people who do not pay the levy cleanliness. The research problems are